`Implementation of Infrastructure Development Policy on the Border (Study at Patama Sebatik Class D Hospital) - Aubert Andika Atmo Prawiradiharjo; Dr. Tjitjik Rahaju, M.Si. Tjitjik; Dr. Indah Prabawati, S.Sos. Prabawati; Ahmad Nizar Hilmi, S.AP., MPA. Nizar (Publika, 2026)
The development of health infrastructure in border areas is a strategic agenda to ensure sovereignty and reduce community dependence on neighboring countries' health facilities. This study aims to analyze the implementation of the policy for the construction of the Class D Pratama Sebatik Hospital, Nunukan Regency, using the Van Meter and Van Horn implementation model. The research method used is descriptive qualitative with data collection through interviews, observation, and documentation. The results of the study indicate a gap between policy objectives and field reality. Despite a high level of commitment (disposition) from implementers, implementation is hampered by resource and environmental variables. The main obstacles include: (1) Implementation of human resources influenced by regulations on honorary workers and dependence on specialist doctors assisted by the central government; (2) Budget management due to non-BLUD status; and (3) Suboptimal cross-sector communication resulting in the main road access to the hospital being in a state of severe disrepair. In conclusion, the physical construction of the hospital building is ineffective without the support of an infrastructure ecosystem and bureaucratic flexibility, resulting in people still choosing to seek treatment in Tawau, Malaysia. Keywords: Policy Implementation, Border Infrastructure, Primary Hospital, Sebatik Island, Van Meter and Van Horn.